Competitive Strategic Performance Benchmarking (CSPB) Model for International Construction Companies - Ercan, Tugce; Koksal, Almula (ELSEVIER, 2016)
Strategic performance management is an important tool in acquiring managerial superiority that affects international construction companies' success. Most comparative analysis of company performance focus on construction site productivity or project management processes, while only few studies focuses on the issues of competitiveness. In this context the objective of this study is to develop a Competitive Strategic Performance Benchmarking (CSPB) model for large international construction companies. The model was developed in two stages. In the first stage, the key parameters of the strategic performance measurement system were developed. In the second state, international construction companies performed self-assessments of their strategic performances on the bases of the key parameters defined in the first stage. Binary logistic regression analysis was employed to develop the strategic performance scale. The findings of this research indicate that a company's competitiveness based on profitability and sales growth are affected by the strength of strategies at the functional level whereas market share is influenced at the competitive level. Finally, a case study was conducted in order to present the applicability of the model for the practitioners. The CSPB model contributes to the managerial decision making process in construction companies and can be used as a tool for strategy formulation.
Keywords: strategic performance; benchmarking; construction company; international construction; binary logistic regression analysis; MANAGEMENT; SERVICES; Engineering